2012
DOI: 10.1371/journal.pone.0053210
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Stimulates Cardiac Regeneration via Cardiomyocyte Proliferation in Experimental Heart Failure

Abstract: Although the adult heart likely retains some regenerative capacity, heart failure (HF) typically remains a progressive disorder. We hypothesise that alterations in the local environment contribute to the failure of regeneration in HF. Previously we showed that nerve growth factor (NGF) is deficient in the failing heart and here we hypothesise that diminished NGF limits the cardiac regenerative response in HF. The capacity of NGF to augment cardiac regeneration was tested in a zebrafish model of HF. Cardiac inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 33 publications
0
29
0
2
Order By: Relevance
“…Lockhart et al reported that NGF plays both acute and long-term roles in the regulation of developing sympathetic synapses in the cardiac system (Lockhart et al, 1997). It was previously shown that NGF augments cardiomyocyte proliferation and may play an important role in cardiac regeneration (Lam et al, 2012). Quirici et al explained that low-affinity nerve growth factor receptor (L-NGFR or CD271) defines a subset of cells with high proliferative, clonogenic, and multipotential differentiation ability in adult bone marrow and adipose tissue (Quirici et al, 2002(Quirici et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lockhart et al reported that NGF plays both acute and long-term roles in the regulation of developing sympathetic synapses in the cardiac system (Lockhart et al, 1997). It was previously shown that NGF augments cardiomyocyte proliferation and may play an important role in cardiac regeneration (Lam et al, 2012). Quirici et al explained that low-affinity nerve growth factor receptor (L-NGFR or CD271) defines a subset of cells with high proliferative, clonogenic, and multipotential differentiation ability in adult bone marrow and adipose tissue (Quirici et al, 2002(Quirici et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Another study performed by Lam et al indicated that the stimulative regenerative response in failing zebrafish heart of NGF was mediated by stimulation of cardiomyocyte proliferation (Lam et al, 2012). It is thought that NGF increased cardiomyocyte proliferation via inactivating the glycogen synthase kinase-3 beta (GSK-3β) pathway (Lam et al, 2012). Tseng et al reported that the βARs were involved in regulation of neonatal cardiomyocyte proliferation and that this mitogenic control might be mediated via the p70 ribosomal protein S6 kinase (p70 S6K) pathway (Tseng et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This seminal finding, published in Brain Research in 1977, has triggered the study on neuroimmune connections, leading to today's accumulation of compelling evidence that NGF is wider than the neuron (paraphrasing Emily Dickinson's The brain is wider than the sky). That is, in addition to its neurotrophic function, this talented molecule influences the survival and activity of a large number of "unpredictable", non-neuronal cells such as immune cells, fibroblasts, epithelial cells, pancreatic beta cells, adipose tissue cells, and cardiomyocytes (6,(9)(10)(11)(12)(13)(14)(15). Such non-neuronal actions of NGF, and also of other neurotrophic factors subsequently discovered, open novel avenues in the study of neurobiology, namely, neuroimmunology (8) and, recently, neuroadipology (16).…”
Section: Ngf-ome or The Multiple Life Of Ngfmentioning
confidence: 99%
“…Several therapeutic strategies for delivery of NGF in animal models and in human diseases have been explored and clinical steps have been attempted, while others are currently in progress to evaluate whether NGF and/or TrkA receptor agonists can prevent or protect against cell degeneration in the nervous system, visual system, cutaneous and myocardial tissue (14,15,19,(22)(23)(24)(25)(26)(27)(28). It most likely exerts therapeutic effects on cardiometabolic diseases such as atherosclerosis, obesity, type 2 diabetes and metabolic syndrome (29)(30)(31).…”
Section: Ngf-ome or The Multiple Life Of Ngfmentioning
confidence: 99%